Factors Affecting Book-Tax Differences in Indonesian Manufacturing Industries - ., Irwan; Murwaningsari, Etty (Journal of Accounting, Business and Finance Research, 2021)
The motivation behind this investigation was to determine the effect of earnings management and tax management on book-tax differences (BTD) and audit fees. The research uses secondary data from the annual financial reports of manufacturing entities from 2015 to 2019 which are recorded on the Indonesia Stock Exchange. The study used a purposive sampling selection method to select 112 samples over a five-year period (2015–2019). Data processing was performed using path analysis techniques at a significance level of 0.05. The uniqueness of this study comes from the use of audit fees as a moderating variable, with the consideration that audit fees have an impact on the preparation of financial reporting. The research results explain that tax management has an effect on BTD. Tax management provides an opportunity for companies to carry out tax planning based on tax law in order to embezzle tax sanctions and make tax payments efficient. However, audit fees do not significantly strengthen the relationship between earnings management or tax management on BTD.